Knowledge and practices of women with obstetric fistula repair on post operative complications and management at Zomba Central Hospital. - Sagawa, Jonas (Kamuzu University of Health Sciences, 2022)
The purpose of the study was to explore the knowledge and practices of women with obstetric fistula repair on post operative complications and management at Zomba Central Hospital. This is an exploratory study that used a qualitative approach. The study was conducted at Zomba Central Hospital, gynaecological ward 2/3. Ten women who had undergone obstetric fistula repair were purposefully included in the study. Data was collected using qualitative approach through face to face individual in-depth interviews using a semi-structured interview guide. All the interviews were recorded using a cell phone recorder and also short hand notes.